Technicians - turf and ornamental - Skoglund, L. G., author; Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
Pesticide Applicators Act, State of Colorado Title 35 Article 10. This fact sheet outlines who turf and ornamental technicians are and how they are trained as defined by the Colorado Applicators Act.
Who are turf and ornamental technicians and how are they trained?
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticide applicators (Persons) -- Licenses -- Colorado; Pesticides -- Application -- Colorado; Pesticides